2016
DOI: 10.18632/oncotarget.13283
|View full text |Cite
|
Sign up to set email alerts
|

SENP1 regulates PTEN stability to dictate prostate cancer development

Abstract: SUMO protease SENP1 is elevated in multiple carcinomas including prostate cancer (PCa). SENP1 exhibits carcinogenic properties; it promotes androgen receptor-dependent and -independent cell proliferation, stabilizes HIF1a, increases VEGF, and supports angiogenesis. However, mice expressing an androgen-responsive promoter driven SENP1-transgene (SENP1-Tg) develop high-grade prostatic intraepithelial neoplasia, but not carcinoma. We now show that tumor suppressive PTEN signaling is induced in SENP1-Tg to enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 40 publications
0
20
1
Order By: Relevance
“…Mus81 SUMOylation is important for normal mitotic chromosome congression, and cells expressing SUMO-resistant Mus81 mutants exhibit compromised DNA damage responses related to tumorigenesis ( 80 ). SENP1 exhibits carcinogenic properties associated with the promotion of androgen receptor-dependent and -independent cell proliferation, the stabilization of hypoxia-inducible factor (HIF)1α, an increase in vascular endothelial growth factor (VEGF) expression and the support of angiogenesis ( 81 ). Ubc9, PIAS1 and SENP1 are highly expressed in human prostate cancer specimens and are associated with hypoxia-inducing factor 1alpha (HIF1α) expression, and SENP1 enhances prostate epithelial cell proliferation.…”
Section: Sumo and Cancermentioning
confidence: 99%
“…Mus81 SUMOylation is important for normal mitotic chromosome congression, and cells expressing SUMO-resistant Mus81 mutants exhibit compromised DNA damage responses related to tumorigenesis ( 80 ). SENP1 exhibits carcinogenic properties associated with the promotion of androgen receptor-dependent and -independent cell proliferation, the stabilization of hypoxia-inducible factor (HIF)1α, an increase in vascular endothelial growth factor (VEGF) expression and the support of angiogenesis ( 81 ). Ubc9, PIAS1 and SENP1 are highly expressed in human prostate cancer specimens and are associated with hypoxia-inducing factor 1alpha (HIF1α) expression, and SENP1 enhances prostate epithelial cell proliferation.…”
Section: Sumo and Cancermentioning
confidence: 99%
“…SENP1 expression is regulated both androgen dependent and independent, and increased SENP1 expression could also potentiate both androgen dependent and independent prostate cancer cells growth [20]. A recent study suggested that SENP1 could modulate the stability of the tumor suppressor gene PTEN to regulate prostate epithelial cell apoptosis [21]. SENP1 inhibits ubiquitylation and degradation of PTEN via deSUMOylation, which is similar to the case of CSR1.…”
Section: Discussionmentioning
confidence: 81%
“…SENP1 regulates cell apoptosis in prostate epithelia. [12] The low levels of SENP1 were essential for the maintenance of stemness in osteosarcoma stem cells, and SENP1 overexpression led to a significant increase in the sensitivity of osteosarcoma stem cells to the herpes simplex virus 1 thymidine kinase gene in combination with ganciclovir in vitro and in vivo. SENP1 plays an important role in regulating genes that are important for cancer development and progression [13].…”
Section: Discussionmentioning
confidence: 98%